(untitled) (Journal of Face Aesthetics, 2023)
Introduction. Appearance is an important element of both the physical and psychological spheres of a person. Clinicians are increasingly using platelet‑rich fibrin (PRF) in aesthetic medicine procedures. PRF can be used to improve the smile with great success. Aim. The aim of this study is to present the latest reports on the use of platelet‑rich fibrin in smile aesthetics from the last 5 years. Material and methods. Online databases were searched by typing the keyword platelet‑rich fibrin and adding words with treatments used in smile aesthetics. The time interval was defined as between 2017–2022. Results. Twelve scientific articles on the use of platelet‑rich fibrin in bone defect regeneration, gingival recession coverage, bifurcation regeneration and tissue regeneration after tooth extractions were used. Conclusions. Platelet‑rich fibrin is widely used in dentistry and has the added value of being autologous.